Agile Local Government: Lessons from Digital Collaborative Service in Jambi City - Winata, Ginazar Hasta; Yusuf, M.; Subekti, Dimas; Wahid, Makmun; Saadah, Mar Atun (Jurnal Manajemen Pelayanan Publik, 2026)
This article explores the implementation of agile government principles in the context of digital collaborative services for building permits in Jambi City. Agile Government prioritizes responsiveness and adaptability in public administration to address the evolving needs of society. This study aims to analyze how these principles can improve the building permit process by enhancing inter-agency collaboration. It identifies key challenges in coordination among government institutions and assesses the extent to which flexibility, openness, and user-orientation have been applied in the service process. Using qualitative methods, this research collected data through interviews and analysis of various documents. Our study indicates that bureaucratic complexity and weak inter-agency communication are major barriers to efficient public service efficiency. However, the use of information technology is considered to have significant potential to improve transparency, coordination, and fast in decision-making. The findings of this study have significance for bureaucratic reform at the local level and propose strategies such as the alignment of Standard Operating Procedures (SOPs), the development of integrated communication platforms, as well as the utilization of real-time monitoring systems to improve efficiency, and quality of public services. These recommendations are not only relevant for Jambi City but can also be applied in other regions facing similar challenges, thus promoting more adaptive, efficient, and user-oriented.